2020
DOI: 10.1093/fampra/cmaa076
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of general practitioners’ single-lead electrocardiogram interpretation skills: a case-vignette study

Abstract: Background Handheld single-lead electrocardiograms (1L-ECG) present a welcome addition to the diagnostic arsenal of general practitioners (GPs). However, little is known about GPs’ 1L-ECG interpretation skills, and thus its reliability in real-world practice. Objective To determine the diagnostic accuracy of GPs in diagnosing atrial fibrillation or flutter (AF/Afl) based on 1L-ECGs, with and without the aid of automatic algor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…Adequate ECG interpretation is paramount to make adequate referral and/or treatment decisions, which means that GPs must have competence in ECG interpretation. Unfortunately the ECG interpretation skill of GPs is not on par with that of cardiologists, 17 , 18 , 19 , 20 , 21 with previous work indicating that GPs incorrectly assess 1 in 5 normal ECGs as abnormal. 22 We saw that PMcardio was especially reliable in assessing presence or absence of AF.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Adequate ECG interpretation is paramount to make adequate referral and/or treatment decisions, which means that GPs must have competence in ECG interpretation. Unfortunately the ECG interpretation skill of GPs is not on par with that of cardiologists, 17 , 18 , 19 , 20 , 21 with previous work indicating that GPs incorrectly assess 1 in 5 normal ECGs as abnormal. 22 We saw that PMcardio was especially reliable in assessing presence or absence of AF.…”
Section: Discussionmentioning
confidence: 93%
“… 22 We saw that PMcardio was especially reliable in assessing presence or absence of AF. Given the mixed evidence on GPs’ ability to assess AF on ECG signal, 17 , 20 , 21 , 22 PMcardio could be of particular use for AF diagnosis as well as AF management when combined with PMcardio’s guideline-directed treatment recommendation module.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent meta-analysis found pooled sensitivities and specificities of automated ECG diagnoses of 89% and 99% respectively in the community setting (24). The accuracy of manual diagnoses has varied greatly between previous studies, with sensitivities and specificities in comparison to reference 12-lead ECGs reported as: 77.4% and 73.0% (22), 90% and 79% (21), 76-92% and 84-100% (20), 89-100% and 85-88% (25), 92.5% and 89.8% (26), 93.9% and 90.1% (18), 100% and 94% (13), and 100% and 100% (27). In all of these studies, the single-lead ECGs were recorded under supervision.…”
Section: Discussionmentioning
confidence: 99%
“…Such 1L-ECG devices showed to be highly accurate in diagnosing AF when interpreted by expert readers (Duarte et al ., 2019 ; Himmelreich et al ., 2019 ). While GPs safely ruled out AF (negative predictive value: 98.8%), they misclassified AF in about half of suspected cases (positive predictive value: 45.7%) (Karregat et al ., 2021 ). Therefore, 1L-ECG devices offer a promising tool for accessible and immediate ECG recordings, as long as GPs have access to an expert reader for consultation.…”
Section: Introductionmentioning
confidence: 99%